Tuberculosis of the Penis: A Review of the Literature - Anthony Kodzo-Grey Venyo (Scientifica)
Background. Tuberculosis of the penis (TBP) is rare. Aim. To review the literature. Method. Various internet data bases were searched. Literature Review. TBP could be primary or secondary, may develop following circumcision performed by a person who had pulmonary Tb, and may be transmitted to the penis from ejaculation, contamination from clothing, or from contact with endometrial secretions, following an earlier pulmonary Tb or Tb elsewhere. TBP presents with a painless/painful small nodule, ulcer, mass on penis which gradually enlarges, and induration/swelling of penis, with or without erectile dysfunction. Inguinal lymph nodes may or may not be palpable. The patient’s voiding is normal. There may or may not be history of circumcision, pulmonary Tb, and BCG immunization. TBP mimics penile carcinoma, granulomatous syphilis penile ulcer, genital herpes simplex, granuloma inguinale, and HIV infection. Diagnosis is established by microscopic examination finding of granulomas +/−AFB in penile discharge or biopsy of lesion or culture of Tb organism from discharge or biopsy specimens or positive Elisa serology/PCR for Tb. PTBs respond to first- or 2nd-line anti-Tb 6-month treatment. Close contacts should be screened. Extrapulmonary Tb should be excluded. Conclusions. Clinicians should consider possibility of PTB in cases of penile lesions and erectile failure.